PENDIDIKAN NILAI LUHUR MELALUI TEMBANG (LAGU) DOLANAN ANAK - Untung Mulyono (SELONDING, 2012)
Education of children of play group and elementary school of age is absolutely required, especially education of affective aspect because it is at the age that they develop their emotional capacity. Continuously trained will develop their emotional capacity and also their ability to control it. Therefore, teachers play a frontline role in developing the character of the children who are not only good in their cognitive and motor aspects, but also in their affective aspect. Traditional children songs, especially the ones for children of schooling age are highly appropriate and it should have been introduced for long time ago. It is because the traditional children songs contain the teachings of noble values and the behavioral aspects that must be developed through real reinforcement, role model and identification. Thus, learning the traditional children song systematically along with teachers will enable the development of good attitude and conduct that they can practice in their family as obligation. Such good conduct and character of noble values must be developed into good behavior, attitude and character. The development of the character of human being plays a strategic role in developing a good conduct. Developing honesty, trust, transparency and wisdom is important for human being that they have high dignity. It is expected that good and right character education will result in high civilized and dignity society. Traditional children songs for the children of play group and elementary school of age play an important role in developing the affective aspect, psychomotor aspect and cognitive aspect of the children and it is a means to develop good character, attitude and behavior based on noble values. Key words: education, noble values and traditional children songs